Adani Power Limited (B) : renegotiating long-term energy contracts - Pandey, Ajay, (SAGE Knowledge. Cases., 2017)
This three-part case series covers a period of over three years during which Adani Power Limited, an independent power producer in India tried to obtain financial relief after having entered into three long-term contracts of 25 years to supply electricity at a fixed price for a total capacity of 3424 MW.